Menganalisis Rasio terhadap Laporan Keuangan pada PT. Unilever Indonesia Tbk - Adinda Rizqi Nur Azizah; Afrida Rosa Marsela; M. Thoha Ainun Najib (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
This research aims to analyze the financial performance of PT. Unilever Indonesia Tbk during the period of 2022-2023 using financial ratios. The method used is the analysis of liquidity, solvency, and profitability ratios towards the company's financial statements. The results show that in terms of liquidity, the company's ability to meet short-term obligations is still poor and tends to deteriorate. Meanwhile, the company's leverage level is quite high, exceeding industry standards. However, in terms of profitability, the performance of PT Unilever Indonesia is quite encouraging with profit margin, return on investment, and return on equity ratios above industry standards. Overall, despite its high profitability, the company needs to improve its liquidity and capital structure to maintain long-term business continuity.